Nurses – Midwifes Knowledge Concerning Polycystic Ovary Syndrome in Baghdad Hospitals - Aqdas Dawood Salman (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Polycystic ovary syndrome is the most common ovary disorder characterize by complexof health problems that affects women of reproductive age due to hormonal imbalance and metabolicproblems, so nurses have an important role in providing counseling and health education for women inreproductive age.Objectives: To assess nurses knowledge about Polycystic ovary syndrome.Methodology: A descriptive study was conducted on probability sample (systematic random) of (100) nursesand midwife who work in obstetric and gynecological departments from three hospitals at Baghdad City:AL-Karkh maternity Hospital, Al-Elwia Maternity Teaching Hospital and Baghdad Teaching Hospital.Study implemented for the period of February 24th 2015 to April 25th 2015. A questionnaire was usedas a tool of data collection to fulfill with objective of the study and consisted of three parts, includingdemographic characteristics, personal experience with polycystic ovary syndrome, sources of knowledgeregarding polycystic ovary syndrome and knowledge regarding polycystic ovary syndrome. A pilot studywas carried out to test the reliability of the questionnaire and content validity was carried out through the 17experts. Descriptive statistical analyses were used to analyze the data.Results: In general the results of the study revealed that half of nurses were at age group (30-39) years ,(35%) of study sample was Institute of medical technology/nursing, half of study sample work at obstetricand gynecological ward, (55%) of study sample were married and the highest percentage (93%) theirsources of knowledge about Polycystic ovary syndrome from syllabus. Most of the study sample had highassessment level of knowledge about polycystic ovary syndrome.Conclusions: Nurses had high level of knowledge regarding the polycystic ovary syndrome, the reason forthis is due to nursing curriculum was effective in giving scientific knowledge about it.